Identity and territory Jewish perceptions of space in antiquity - Ben-Eliyahu, Eyal; University of California Press (Oakland University of California Press, 2019)
"The book examines the role of territory in Jewish identity in antiquity and, more specifically, the role of Jewish perceptions of space and place in identity. The time period covered extends from the Second Temple period to the first centuries CE. The examination relates to a variety of approaches to the land, its borders, and its holy places as expressed by Jewish writers of the period, located both inside and outside of the land. The book's central assertion is that the territory's status and scope and the way in which sacred spaces are perceived all depend on Jewish identity in all of its complexity and diversity"--Provided by publisher
Introduction : identity, space, place, and territory -- From Judah to Israel : territory and identity -- Borders, space, and identity in Second Temple literature -- From earthly land to holy land -- Land of the sages -- Rabbinic literature confronts non-rabbinic Jewish culture and Christianity: the question of holy spaces
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Space -- Religious aspects -- Judaism; Jews -- Identity -- History -- To 1500; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D